Konsep dan implementasi digital citizenship education di Sekolah Menengah Atas Negeri 4 Kota Malang - Febrilio, Erlang Prawidha; Wibowo, Arif Prasetyo; Budiono, Budiono (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to explain the concept and implementation of Digital Citizenship Education in Malang City State High Schools. Qualitative methods with a descriptive approach were used in this research. The research location is at SMAN 4 Malang City. The data collection technique is conducting interviews with students, teachers of Pancasila and Citizenship education subjects, and principals at State High School 4 Malang City with research instruments using interview guidelines. The data analysis techniques used were interview, observation and documentation techniques followed by data processing and analysis with the stages of data reduction, verification and data display. The data validity tests carried out are the credibility test, transferability test, dependability test, and confirmability test. The results of this research were found to be (1) Concept of Digital Citizenship Education 2) Implementation of Digital Citizenship Education. The conclusion of this research is that the concept and implementation of Digital Citizenship Education in Malang City State High Schools is by teaching and training students in using technology effectively, namely Digital rights and responsibilities in regulations and culture/activities at school through learning activities and Digital access through providing facilities. to support digital-based learning implemented in schools.